(untitled) (Journal of Partial Differential Equations, 2018)
Let u∈C(R,H^1) be the solution to the initial value problem for a 2D semilinear Schrödinger equation with exponential type nonlinearity, given in [1]. We prove that the L^r norms of u decay as t→±∞, provided that r > 2.